Re‐offending in forensic patients released from secure care: The role of antisocial/borderline personality disorder co‐morbidity, substance dependence and severe childhood conduct disorder. (31st January 2013) - Howard, Rick; McCarthy, Lucy; Huband, Nick; Duggan, Conor
ABSTRACT Background Research suggests that a particular externalising phenotype, manifested in a developmental trajectory from severe childhood conduct disorder through early‐onset substance abuse to adult antisocial/borderline personality disorder co‐morbidity, may increase risk of antisocial behaviour in general and criminal recidivism in particular. Aim This study aims to test the hypothesis that antisocial/borderline co‐morbidity together with the triad of substance dependence, severe conduct disorder and borderline pathology would result in an increased risk of criminal recidivism. Methods Fifty‐three men who had been assessed and treated in a secure hospital unit were followed up after they had returned to the community. They were assessed for severity of the following: (i) antisocial personality disorder; (ii) borderline personality disorder; (iii) drug/alcohol dependence; and (iv) high Psychopathy Checklist Revised scores (factors 1 and 2). Results Patients with antisocial/borderline co‐morbidity took significantly less time to re‐offend compared with those without such co‐morbidity. Both Psychopathy Checklist Revised factor 2 and the tripartite risk measure significantly predicted time to re‐offence; the former largely accounted for the predictive accuracy of the latter. Conclusion Risk of criminal recidivism can be adequately assessed without recourse to the pejorative term 'psychopath'. It is sufficient to assess the presence of the three elements of our risk measure: borderline and antisocial personality disorders in the context of drug/alcohol dependence and severe childhood conduct disorder. Practical implications of the study are as follows. (i) Sound assessment of personality, inclusive of a detailed history of childhood conduct disorder as well as adolescent and adult substance misuse, yields good enough information about risk of recidivism without recourse to the pejorative concept of 'psychopathy'. (ii) Given the high risk of alcohol‐related violence in individuals with antisocial/borderline co‐morbidity, there is a need for specific alcohol‐directed interventions to help such men retain control of their substance use. Copyright © 2013 John Wiley & Sons, Ltd.